Mengulas Relasi Mayoritas dan Minoritas dalam Kehidupan Beragama di Indonesia Menurut Filsafat Wajah Emmanuel Levinas - Jugan, Wenseslaus; Pandor, Pius; Riyanto, F. X. Eko Armada; Amabugis, Heribertus; Santos, Charolus G. D. (Jayapangus Press, 2025)
The main focus of this research is to understand and examine the relationship between majority and minority groups in religious life in Indonesia. The author uses Levinas' philosophy of the face as a kind of analytical tool to explore and delve into this issue. The purpose of this paper is to reconstruct the relationship between majority and minority groups in Indonesia’s religious life through Levinas' thoughts, so that society can better understand religious coexistence amidst existing pluralism. The methodology used in this paper is library research. This paper finds that Emmanuel Levinas' concept of the philosophy of the face emphasizes the importance of the presence of “the Other” in human relationships. In Indonesia's religious life, this thought contributes to addressing the phenomenon of majority-minority relations that lead to radicalism, identity politics, terrorism, and the reduction of the presence of others, by stressing ethical responsibility in overcoming power relations. The philosophy of the face opens opportunities for humanistic dialogue, encourages respect for the Other, and fosters a harmonious religious life. Dialogue with people of different religions will increasingly enable individuals to better embrace pluralism. Moreover, its implementation in the Indonesian context does face challenges. Therefore, the thoughts of Hannah Arendt and Martin Buber can assist society in building a more inclusive and harmonious majority-minority relationship. In conclusion, Levinas' philosophy of the face serves as an inspiration to encourage ethical awareness, dialogue, and respect for “the Other” in Indonesia’s pluralistic society. This effort must also be supported by interdisciplinary approaches, incorporating thoughts from other philosophers and utilizing other sciences to address majority-minority issues in Indonesia.